Association of Interpersonal Violence With Self-Reported History of Head Injury - Stoddard, Sarah A. (American Academy of Pediatrics, 2011)
OBJECTIVE: The purpose of this study was to examine differences in interpersonal violence among individuals who reported a head injury compared with those who did not report a head injury. METHODS: We used data from an 8-year longitudinal study of youth selected by their grade point average to study those at-risk for high school dropout in 4 public high schools in a Midwestern city (N = 850). Participants were followed up from mid-adolescence to the transition into young adulthood. One-way analyses of variance were used to test for differences in levels of interpersonal violence, and repeated measures multivariate analyses of variance were used to assess differences in levels of violence over time among participants based on reports of head injury. A series of multivariate regression analyses examined whether head injury was associated with subsequent violent behavior. RESULTS: Participants who had ever experienced a head injury before young adulthood reported more interpersonal violence in young adulthood than participants who had never had a head injury. In multivariate analyses, respondents who had a head injury in the past year reported more subsequent interpersonal violence than respondents who had not had a head injury. CONCLUSION: Our findings support other studies that link history of head injury to later interpersonal violence.